Taqman real-time polymerase chain reaction for the determination of pork adulteration in meat nuggets - Md. Eaqub, Ali; Uda, Hashim, Prof. Dr.; Shuhaimi, Mustafa, Assoc. Prof. Dr.; Yaacob, Che Man, Prof. Datuk Dr.; Md. Abdul, Latif, Dr.; Khondaker, Nurul Islam; Md. Zuki, Abu Bakar, Prof. Dr.; Md. Majibar, Rahman (Vup Food Research Institute, 2013)
Link to publisher's homepage at http://www.vup.sk/en/